Effect of Laser Exposure on Structural and Optical Properties of CdO and Li Doped CdO Nano Structured Thin Film Synthesized by Sol Gel Method - Farooq, W. A.; AL-Otaibi, L. R.; Al-Dwayyan, A. S.; Yakuphanoğlu, Fahrettin; Atif, M. (Amer Scientific Publishers, 2016)
Nano structured thin film of CdO and Li doped CdO have been synthesized by sol-gel spin-coating method on amorphous glass substrates. The samples were irradiated with laser beam from pulsed Q-switched Nd:YAG laser of pulse width of 7 ns and repetition rate of 10 Hz at wavelength of 1064 nm. Effect of laser irradiation on structural and optical properties of these samples was investigated. The laser irradiation effect on morphology and microstructure was carried out with scanning microscope (SEM) and XRD respectively. Grain sizes were calculated with Scherrer formula. Optical properties were investigated via absorption, photoluminescence, calculation of bad gap and refractive indices. Agglomerations of nano particles are observed in SEM images after laser irradiation.
Keywords: Laser Irradiation; Agglomeration; Microstructure